EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM-ASSISTED INDIVIDUALIZATION (TAI) DAN TEAMS GAMES TOURNAMENTS (TGT) PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KEMAMPUAN SPASIAL SISWA KELAS VIII MTs NEGERI SE-KABUPATEN NGAWI - Wahyuniar, Lilia Sinta; Budiyono, Budiyono; Sari S, Dewi Retno (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objectives of this research was to investigate the effect of the learning models on the learning achievement in Mathematics viewed from the spatial ability of the students. The learning models compared were the cooperative learning model of the TAI type, the cooperative learning model of the TGT type, and the direct learning model. This research used the quasi experimental research method with the factorial design of 3 x 3. Its population was all of the students in Grade VIII of Islamic State Junior Secondary Schools of Ngawi regency. The samples of the research consisted of 336 students from Islamic State Junior Secondary School of Paron, Islamic State Junior Secondary School of Ngawi, and Islamic State Junior Secondary School of Geneng. They were taken by using the stratified cluster random sampling technique. The instruments to gather the data of the research were test of learning achievement in Mathematics and test of spatial ability. The proposed hypotheses of the research were tested by using the two-way analysis of variance with unbalanced cells. The results of the research were as follows. 1) The cooperative learning model of the TAI type results in a better learning achievement in Mathematics than the cooperative learning model of the TGT type and the direct learning model, and the cooperative learning model of the TGT type results in a better learning achievement in Mathematics than the direct learning model. 2) The learning achievement in Mathematics of the students with the high spatial ability was better than that of the students with the moderate and low spatial abilities, and the learning achievement in Mathematics of the students with the moderate spatial ability was better than that of the students with the low spatial ability. 3) There was an interaction the aforementioned learning models and the categories of the spatial ability on the learning achievement in Mathematics of the students.Keywords: TAI, TGT, and spatial ability.